Evaluation of children with urolithiasis - Syed A.H Rizvi; Sajid Sultan; Mirza N Zafar; Bashir Ahmed; Syed M Faiq; Kehkashan Z Hossain; Syed A.A Naqvi (Indian Journal of Urology, 2007)
Objectives: To describe an evaluation protocol for pediatric stone formers for risk assessment and management strategies. Materials and Methods: Between 2002-2006, 2618 children of age three months to 15 years were evaluated for stone disease. Evaluation included demographics, history, anthropometry, diet, ultrasound, X-ray KUB, IVU, blood and 24h urine chemistry and cultures. Stones were analyzed by IR spectroscopy. Results: The median age was seven years with a M:F ratio of 2.2:1. Of the 2618 patients, 2216 presented with normal renal function and 402 with renal failure. Main symptoms were abdominal pain (33%), flank pain (38%) and fever (38%). Renal failure patients also had shortness of breath (38%) and oligo-anuria (26%). Children were malnourished with height and weight deficits in 65% and 76% respectively. Diet was low in protein (74%), calcium (55%) and fluids in (55%), high in oxalate (55%), sodium (39%), purines (42%) and refined sugar (41%). Overall urine cultures were positive in 1208 (46%) with E. coli (38%) and Klebsiella (8%). Stone distribution was renal in 64%, ureter in 8%, bladder in 18%, bilateral in 40% and multiple sites in 18%. Median stone size was> 1.5-2.0 cm. The frequency of compounds in stones was ammonium urate (58%), calcium oxalate (63%), uric acid (6%), calcium phosphate (12%) and struvite (8%). Metabolic abnormalities included hypovolumia (31%), hypocitraturia (87%), hyperoxaluria (43%) and hyperuricosuria (26%). Dietary and medical treatment corrected risk factors in two-thirds of patients with a recurrence rate of about 1.15%. Conclusion: An evaluation based on history, imaging, diet, metabolic analysis and stone type can help to tailor management strategies.